The Alienation of the Armed Conflict in Bogotá, Colombia (1948-1991) - Escobar Moyano, Carlos Andrés (2026)
This article analyzes the relationship between urbanization and armed conflict in Bogotá (1948-1991) through a historical-critical lens. It argues that the city was not a marginal stage but a constitutive actor of the conflict, where violence operated as a structural mediation in the production of urban space. The study challenges the analytical alienation of the urban dimension in dominant narratives—often limited to rural explanations—and introduces the notion of “spatialization of violence” to explain internal borders, segregation, and coercive governance. Based on historical evidence, it examines authoritarian modernization, informal settlements, popular protest, and the securitarian turn of the State. It concludes that integrating the urban dimension is essential to understanding the persistence of conflict and designing peace policies grounded in spatial justice.